Assessment of Hematological Profile of Patients with Enteric Fever - An Observational Study (The Planet, 2023)
Introduction: Enteric fever, also known as typhoid fever, isa contagious illness that affects the entire body.Haemoglobin, a crucial component of red blood cellsnecessary for oxygen transmission, is frequently impactedby enteric fever. Through an observational approach, thecurrent study sought to identify the haematological profileof individuals with enteric fever. Methods and materials:This observational cross-sectional study was conducted atthe Department of Medicine, Bangladesh Medical College,Hospital, Dhaka, Bangladesh. The study duration was 3months from June 2022 to August 2022. Result: Among thestudy population (N=50), most of them 56.00% were 18 to29 years old. About half of the study population 52.00%were male. The majority of the study population 52.00%were students. Eighteen 36.00% were married. Most of thestudy population 86.00% came from urban areas. Among the respondents, six 12.00% haddiabetes, and four 8.00% had bronchial asthma. The mean duration of fever reported by therespondents was approximately 6.98 days. Based on CBC findings, the mean hemoglobin,RBC was 13.14, 4.79 respectively. Based on White Blood Cell Variables, the mean total WBC(10^9/L), neutrophil, and lymphocytes, were 6.75, 71.33, and 23.67 respectively. Conclusion: The study found that enteric fever can have a considerable impacton haematological markers. Salmonella Typhi's entry into the bloodstream triggers aninflammatory reaction that changes several haematological markers. Monitoringhaemoglobin levels can aid in assessing the condition's severity and guiding the mosteffective therapeutic modalities.
Keywords: Enteric fever; Hemoglobin; Blood cells